Training in Marketing Strategies through Digital Marketing for Scaling Up Businesses of Silver Craft SMEs in Banda Aceh City - Lautania, Maya Febrianty; Darwanis, Darwanis; Ariani, Nita Erika; Linda, Linda; Afrianandra, Cut; Fitri, Meutia (PT FORMOSA CENDEKIA GLOBAL, 2024)
In today's digital era, digital marketing strategies are crucial, particularly for Small and Medium Enterprises (SMEs). The primary objective of this training is to equip participants with essential knowledge and skills for implementing effective digital marketing strategies, with the ultimate goal of enhancing the business scale of SMEs. Conducted over two days, from October 9 to 10, 2023, the training emphasized introducing and teaching various digital marketing applications, such as Facebook and Instagram. It also provided guidance on creating engaging content for marketing their products. By the end of the training, the participant, CV Taufik Perak, had successfully established digital marketing accounts on several social media platforms.